The Greek community of Sfax and Djerba in Tunisia between 1890 and 1940 and its role in the local economy. Issue 1 (1st January 2017) - Chaldeos, Antonios
ABSTRACT: Although the Greek presence in Tunisia dates back to the middle of the sixteenth century, when merchants and ex-slaves settled in the port of Tunis, the Greeks settled in Sfax only in the last half of the nineteenth century. The political changes in the eastern Mediterranean and the economic upheavals in the international market, particularly between 1890 and 1930, greatly affected the economy of Sfax and its cultural identity. As the demand for sponges increased, a large number of Greeks settled in Sfax. This resulted in the transformation of the seasonal sponge industry into an organised business. The article analyses the wider political and economic conditions that defined the formation of the Greek community in Sfax. It discusses the role of the Greeks in the local economy and their contribution to the transformation of Sfax into a major trade centre of North Africa. Since there is little information about the Greek presence in the official history of Sfax, we will bring forward new insights and facts.